2021
DOI: 10.3389/fcvm.2021.735637
|View full text |Cite
|
Sign up to set email alerts
|

Visceral Adiposity Index Plays an Important Role in Prognostic Prediction in Patients With Non-ST-Segment Elevation Acute Coronary Syndrome and Type 2 Diabetes Mellitus Undergoing Percutaneous Coronary Intervention

Abstract: Background: Visceral adiposity index (VAI), a surrogate marker of adiposity and insulin resistance, has been demonstrated to be significantly related to cardiovascular disease. It remains indistinct whether VAI predicts adverse prognosis after percutaneous coronary intervention (PCI) for patients with non-ST-segment elevation acute coronary syndrome (NSTE-ACS) and type 2 diabetes mellitus (T2DM).Methods: A total of 798 participants who met the enrollment criteria were finally brought into this study. VAI was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 58 publications
(77 reference statements)
0
2
0
Order By: Relevance
“…Previous studies have shown that the visceral adiposity index (VAI) is a better predictor of clinical and coronary angiographic severity assessment in patients with ACS than other obesity indices [ 31 ]. VAI is determined by WC, BMI, fasting triglycerides (TG), and high-density lipoprotein cholesterol [ 32 ]. Compared with peripheral adiposity (BMI), central adiposity (WC) was more predictive in ACS patients [ 33 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the visceral adiposity index (VAI) is a better predictor of clinical and coronary angiographic severity assessment in patients with ACS than other obesity indices [ 31 ]. VAI is determined by WC, BMI, fasting triglycerides (TG), and high-density lipoprotein cholesterol [ 32 ]. Compared with peripheral adiposity (BMI), central adiposity (WC) was more predictive in ACS patients [ 33 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the visceral adiposity index (VAI) is a better predictor of clinical and coronary angiographic severity assessment in patients with ACS than other obesity indices [29]. VAI is determined by WC, BMI, fasting triglycerides (TG), and high-density lipoprotein cholesterol [30]. Compared with peripheral adiposity (BMI), central adiposity (WC) was more predictive in ACS patients [31].…”
mentioning
confidence: 99%